Clays and Clay Minerals, Vol. 57, No. 4, 416–424, 2009. - Janek, Marian; Bugar, Ignac; Lorenc, Dusan; Szocs, Vojtech; Velic, Dusan; Chorvat, Dusan (My University, 2009)
Micaceous layer silicate clay minerals are attractive materials for applications involving nonlinear optics because of their low cost and ability to form well ordered, platy aggregates, but such applications require precise knowledge of the dielectric behavior of the clay. The purpose of the present study was to use Terahertz time-domain spectroscopy (THz-TDS) to determine the dielectric properties of certain cleavable layered clay minerals, including muscovite, vermiculite, phlogopite, and biotite. The samples were characterized by X-ray diffraction and Fourier transform infrared spectroscopy as well as chemical analysis by Energy dispersive X-ray spectroscopy. The THz frequency window investigated was the far-infrared region of 3.3 to ~40.0 cm 1 corresponding to 0.1 and 1.2 THz, respectively. The samples were selected so that the hydrated form of the interlayer cation, e.g. Mg2+ present in the interlayer gallery of vermiculite, could be compared to species such as phlogopite, biotite, and muscovite with the dehydrated form of interlayer cations such as K+ or Na+. The frequency-dependent complex index of refraction of these natural materials was determined to vary between 2.50 and 2.80. The presence of water in the interlayer space of vermiculite was reflected in the detection of increased values of the absorption index in comparison with the muscovite, phlogopite, and biotite.
Terahertz Time-domain Spectroscopy Of Selected Layered Silicates
gsccm57402-jan.pdf-- 313KB
Keywords: Periodicals; Geology; Absorption Index; Biotite; Far-infrared; Index of Refraction; Layered Silicates; Muscovite; Phlogopite; THz-TDS; Vermiculite